Stepping Out on Faith: Interview with Coquie Hughes - Welbon, Yvonne (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
I grew up on the West Side of Chicago, where it was infested with gangs and drugs and violence. But I was always the type of person that wanted to be better than my environment, and I was also the type of person that didn’t want people to underestimate me because of where I came from. And so I made up in my mind, even as a young child, that I wanted to be somebody. I love making movies. I’ve wanted to be who I am ever since I saw Sidney Lumet’s movie The Wiz (1978).
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé